Heme Uptake and Utilization by Gram-Negative Bacterial Pathogens - Richard, Kaylie L.; Kelley, Brittni R.; Johnson, Jeremiah G. (Frontiers in Cellular and Infection Microbiology, 2019)
Iron is a transition metal utilized by nearly all forms of life for essential cellular processes such as DNA synthesis and cellular respiration. During infection by a bacterial pathogen, the host utilizes various strategies to sequester iron in a process called nutritional immunity. Gram-negative pathogens have evolved numerous mechanisms to circumvent these host defenses to obtain iron from heme. Gram-negative pathogens must also be able to closely regulate the intracellular concentrations of iron and heme, as increased levels of iron can lead to toxic reactive oxygen species. In this review, we outline systems within Gram-negative bacteria associated with heme transport and utilization, beginning with hemolysis and concluding with heme degradation. We found co-regulation of heme uptake systems with other cellular processes to be complex and not completely understood, in addition to understanding the final fate of heme during infection by Gram-negative pathogens.